Q: How do you solve 5h 2(11-h)-5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

35

5h 10m 13m

4fg^-5 / 5h^-3 = 4fh^3/5g^5

h=16

53 x h3

It is: 12h+5h = 17h

8w x 5h = 40wh

If you mean: 10h+6-5h+3 then it is 5h+9 when simplified

5h+11=13h-21 -5h +21 -5h +21 32=8h /8 /8 4=h

The simplified expression of 10h+6-5h+3 is 5h+9

5h + 6 = 25 Subtract 6 from both sides: 5h = 19 Divide both sides by 5: h = 3.8 h = 3.8

h = 0.538462 14 + 5h + 2h = 5h + 28h 14 + 7h = 33h 14 + 7h - 7h = 33h - 7h 14 = 26h 14/26 = 26/26h 0..538462 = h